2015
DOI: 10.1007/s10008-015-2877-9
|View full text |Cite
|
Sign up to set email alerts
|

The use of a multiscale approach in electrochemistry to study the corrosion behaviour of as-cast AZ91 magnesium alloy

Abstract: The microstructure of as-cast AZ91 alloy is complex, with the presence of Mg 17 (Al, Zn) 12 precipitates surrounded by an eutectic phase, AlMn intermetallic particles and an α-Mg solid solution. In addition, the distribution of aluminium in the alloy was found to be heterogeneous. Under these conditions, a multiscale approach coupling global and local electrochemical measurements seems to be a promising method to study its corrosion behaviour. Results show that the multiscale approach can be used in 0.1 M NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(1 citation statement)
references
References 62 publications
0
1
0
Order By: Relevance
“…The intermetallic phases can behave as cathodic or anodic places depending on their chemical composition. Type, size and distribution of precipitates within the magnesium matrix have a significant influence on the corrosion resistance of Mg alloys [ 21 , 22 , 23 , 24 ]. It was found that good corrosion resistance of Mg alloys can be achieved when structural uniformity is present.…”
Section: Introductionmentioning
confidence: 99%
“…The intermetallic phases can behave as cathodic or anodic places depending on their chemical composition. Type, size and distribution of precipitates within the magnesium matrix have a significant influence on the corrosion resistance of Mg alloys [ 21 , 22 , 23 , 24 ]. It was found that good corrosion resistance of Mg alloys can be achieved when structural uniformity is present.…”
Section: Introductionmentioning
confidence: 99%